The role of health care workers in collaborating with traditional healers in primary health care. Part 2 - Rosemare Troskie (AOSIS, 1997)
In part one of this article the background and research methodology of this study was discussed. Opsomming In deel een van die artikel is die agtergrond tot die studie en die navorsings metodologie breedvoerig bespreek. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.